(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the cost of medications used for type 2 diabetes mellitus treatment among patients covered by health insurance at Thu Duc General Hospital from June 2023 to June 2024. Subjects and methods: A cross-sectional descriptive study was conducted through retrospective data collection related to medication costs for type 2 diabetes mellitus treatment among health insurance-covered patients at Thu Duc General Hospital from June 2023 to June 2024. Medication costs were analyzed by drug classification, country of origin, route of administration, and treatment setting, expressed in total cost values and percentages. Results: During the period from June 2023 to June 2024, the total medication cost for type 2 diabetes mellitus treatment in the study sample was 50.578 billion VND. Outpatient medications accounted for 97.39%; imported medications represented 87.46%; oral medications constituted 68.88%; and single-component medications made up 77.57% of the total cost. Among the 6 main medication groups, Insulin accounted for 31.1% of costs, Biguanide + DPP4i combinations for 15.4%, and SGLT2i for 15.4%. DPP4i had the highest domestic production rate (32.8%); Insulin and SGLT2i were entirely imported, representing 35.58% and 17.67% of total imported medication costs, respectively. Insulin was the only injectable medication; among oral medications, SGLT2i and Biguanide + DPP4i combinations accounted for the highest proportions (22.36% and 22.19%, respectively). Conclusion: The study results indicate that type 2 diabetes mellitus medication costs were predominantly concentrated in imported medications, particularly Insulin and newer agents such as SGLT2i and DPP4i. Oral medications continued to represent a significant proportion of total costs, and the trend of using single-component medications remained more prevalent than combination therapies.